2006
DOI: 10.1080/13636820500507708
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the elective or required status of courses on student evaluations

Abstract: This study examined the impact on a course evaluation of the course being either an elective or a required part of a training programme. Three elective and three required courses were evaluated using both a scaled and an open ended response form. Many variables were taken into account when examining the effect of course status, which other researchers have tended to neglect. These included the type of training method employed, the presenter and the type of student. It was found using a scaled response form tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 12 publications
1
28
0
5
Order By: Relevance
“…To that end, several large studies consistently find teachers of elective courses receive more favorable evaluations than their colleagues teaching required classes (Drago & Wagner, 2004;Whitten & Umble;Pohlmann, 1975;Lovell & Haner, 1955). Researchers have suggested a number of possible reasons for these findings, including student attitudes towards the topic, the quantitative nature of some of the required courses, student perception of quality, the professor's teaching style (Bosshardt, 2001;Marsh & Roche, 1997) and the students interest and engagement (Darby, 2006a); all of which affect STEs. Related research finds STEs to be influenced by a student's year in school; asserting a positive correlation between the two (Ory, 2001).…”
Section: Class Type (Core or Elective)mentioning
confidence: 99%
“…To that end, several large studies consistently find teachers of elective courses receive more favorable evaluations than their colleagues teaching required classes (Drago & Wagner, 2004;Whitten & Umble;Pohlmann, 1975;Lovell & Haner, 1955). Researchers have suggested a number of possible reasons for these findings, including student attitudes towards the topic, the quantitative nature of some of the required courses, student perception of quality, the professor's teaching style (Bosshardt, 2001;Marsh & Roche, 1997) and the students interest and engagement (Darby, 2006a); all of which affect STEs. Related research finds STEs to be influenced by a student's year in school; asserting a positive correlation between the two (Ory, 2001).…”
Section: Class Type (Core or Elective)mentioning
confidence: 99%
“…Previous studies reported that students rate elective courses more favorably than required ones, presumably because students are participating in a course that they have an interest or focus in 6,14 . Hence, course type is another uncontrollable variable that needs to be considered for modeling the student course selection process.…”
Section: Course Typementioning
confidence: 99%
“…Farklı ilgi, ihtiyaç ve yeteneklere sahip öğrencilere programlarda farklı ders seçenekleri sunulmaktadır (EARGED, 2008). Sunulan bu dersler arasında öğrencilerin ilgileri ve beklentileri ile önemli derecede örtüşen seçmeli dersler özü itibari ile öğrenciler tarafından özellikle kişisel gelişim alanında ilgi çekici bulunmaktadır (Darby, 2006). Bilim Uygulamaları dersi Milli Eğitim Bakanlığı tarafından 2012-2013 eğitim öğretim yılından itibaren 5. sınıflardan 8. sınıflara kadar kademeli bir şekilde seçmeli ders olarak konulmuştur.…”
Section: Introductionunclassified
“…Yapılan çalışmalarda eğitimin her kademesinde öğrencilerin, seçmeli derslerin seçiminde de bazı zorluklarla karşılaştıkları belirtilmektedir. EARGED (2008) tarafından yapılan "Seçmeli Derslerin Seçim Kriterlerinin Değerlendirilmesi Araştırması" adlı çalışmaya göre, ilköğretim okullarında seçmeli derslerin belirlenmesinde okulun imkânlarının etkili faktör olduğu ve seçmeli dersler hakkında öğrencilere ve velilere yönelik bilgilendirmenin yetersiz olduğu sonuçlarına ulaşılmıştır (Bozdoğan, Bozdoğan ve Şengül, 2014 (Babad, 2001;Kardan, Sadeghi, Ghidary, & Sani, 2013;Schnabel, Alfeld, Eccles, Köller, & Baumert, 2002;Pass, Mehta, & Mehta, 2012;Wilson, Strocking, & Goldstein, 1993) ve seçmeli derslere yönelik çalışmaların (Darby, 2006;Eyidoğan, Odabaşı ve Kılıçer, 2011;Karagözoğlu, 2015;Öztürk ve Yılmaz, 2011;Taş, 2004;Tezcan ve Gümüş, 2008;Ülgen, 1992) olduğu görülmektedir. Ancak seçmeli derslere yönelik olarak uygulamaya konan Bilim Uygulamaları dersi ile ilgili çalışmaların sınırlı olduğu görülmektedir (Bozdoğan, Bozdoğan ve Şengül, 2014;Çavuş ve Kaplan, 2013;Eke, 2013).…”
Section: Introductionunclassified